System of Additional Professional Education as a Basis of Lifelong Professional Education - S. V. Notova; I. A. Podosenova (Высшее образование в России)
The article considers the implementation of the principle of continuing education through the system of additional professional education at Orenburg State University. Additional professional education is the main element of the system of lifelong education. The authors analyze the current trends in the development of additional professional education in the Russian Federation and the role of higher education in it, as well as the opportunities and problems of implementing additional professional programs at the University. The analysis of the dynamics and structure of additional professional programs of the Orenburg State University is carried out. The mechanisms of implementing additional professional programs based on a practice-oriented integrated approach aimed at strengthening the practical orientation of programs based on the integration of University’s educational activities and strategic partnership with enterprises and organizations of the region are proposed. The authors analyze the possibilities and prospects of using e-learning and technologies of distance education in the implementation of additional professional programs. The article highlights the mandatory conditions for building an effective system of additional professional education at the University, based on close interaction with the program’s customers, the development of professional competencies of teaching staff engaged in the implementation of additional programs, and the active use of modern educational technologies.